(untitled) (Journal of Hama University, 2022)
This study aimed to show the role of strategic Orientation of human resources in the training. To achieve the goal of this study, the descriptive analytical method was relied on as a general approach to research, where 82 questionnaires were distributed to faculty members with administrative positions, and the data was analyzed by the Statistical Package for Economic and Social Sciences (SPSS). The most important results of the search were as follows: • Training courses are not held continuously and in a timely manner for faculty members. • There are administrative facilities for participants in training courses. • The university’s strategic vision does not take into account the satisfaction of the needs and desires of its human resources at the appropriate level. • There is a significant impact of the strategic Orientation of human resources at Tishreen University on the training for faculty members. The researcher recommends that the university develop a strategic orientation towards its human resources, that increases the degree of satisfaction of the needs and desires of its human resources, especially the faculty members, because the more the university pays attention to its human resources, the better the performance of these resources and the greater its desire to continue working at the university.